Schizophrenic Sensemaking as (Non-)Response to Institutional Ambiguity: The Case of the German Child Protection Industry. Issue 1 (1st January 2020) - Bode, Ingo; Turba, Hannu
ABSTRACT: Scholarship on contemporary organizations has dealt with institutional complexity and conflicting demands, stressing the capacity of organizations to find constructive responses to such complexity. However, in human service sectors exhibiting strong ambiguity and logic incompatibility, solutions may be scarce. But what happens instead? Exploring the German child protection industry, its regulatory framework, and organizational dynamics, we argue that, given a permanent clash of the entrenched welfare logic with managerialist prescriptions, major reactions rest upon 'schizophrenic sensemaking' that prompts clueless organizational improvisation. Understanding such collective 'non-response' may help human service managers avoid unjustified accusations regarding professional malpractice and motivate political advocacy.